2021
DOI: 10.1021/acs.inorgchem.1c01839
|View full text |Cite
|
Sign up to set email alerts
|

“Shake ‘n Bake” Route to Functionalized Zr-UiO-66 Metal–Organic Frameworks

Abstract: We report a novel synthetic procedure for the high-yield synthesis of metal–organic frameworks (MOFs) with fcu topology with a UiO-66-like structure starting from a range of commercial Zr IV precursors and various substituted dicarboxylic linkers. The syntheses are carried out by grinding in a ball mill the starting reagents, namely, Zr salts and the dicarboxylic linkers, in the presence of a small amount of acetic acid and water (1 mL total volume for 1 mmol of ea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…S4, ESI †) than UiO-66 (3.03 nm and 0.28 cm 3 g À1 ). As reported in previous works on UiO-66-type MOFs, the surface areas and pore structures could be drastically changed after introducing ligands such as OH, COOH, NO 2 , NH 2 , Br and F. 35,36 This is because of the significant role of the polar properties of different ligands in the crystallization process. The extremely high surface area and porous structure of the asprepared piezoelectric MOFs overcome the disadvantage of conventional piezoelectric materials as catalysts.…”
Section: Resultsmentioning
confidence: 77%
“…S4, ESI †) than UiO-66 (3.03 nm and 0.28 cm 3 g À1 ). As reported in previous works on UiO-66-type MOFs, the surface areas and pore structures could be drastically changed after introducing ligands such as OH, COOH, NO 2 , NH 2 , Br and F. 35,36 This is because of the significant role of the polar properties of different ligands in the crystallization process. The extremely high surface area and porous structure of the asprepared piezoelectric MOFs overcome the disadvantage of conventional piezoelectric materials as catalysts.…”
Section: Resultsmentioning
confidence: 77%
“…This result indicated that the absence of the linker caused the Zr–O cluster to form an electron-deficient state . The decrease of the binding energy of O–CO in O 1s for UiO-67-200 indicated that the electron cloud density of O decreased in the linkers . These results fully indicated that a certain degree of linker defects changed the coordination environment of Zr.…”
Section: Resultsmentioning
confidence: 83%
“…40 The decrease of the binding energy of O−CO in O 1s for UiO-67-200 indicated that the electron cloud density of O decreased in the linkers. 41 These results fully indicated that a certain degree of linker defects changed the coordination environment of Zr. The distributions of C, O, and Zr in all samples were also compared, as shown in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…ZrTFS was prepared with a "Shake 'n Bake" procedure that we have previously employed for the synthesis of several UiO-66 MOF analogues. 54 In this procedure, a dense slurry of reagents in a small amount of a liquid is obtained instead of a clear solution upon a preliminary treatment using a ball mill. This probably induces a partial MOF crystallization before the heating stage, which provides a crystalline material at the end of the synthesis.…”
Section: Synthesis and Structural Characterization Of Zr-tfsmentioning
confidence: 99%